Comprehensive impact assessment of soil fertility enhancement strategies, economic viability, and yield performance of tomato (Solanum lycopersicum) in sub-tropical hill agroecosystems of Manipur - SINGH, PH CHANDRAMANI; BHUPENCHANDRA, INGUDAM; CHATURVEDI, ABHIMANYU; SINGH, L SOMENDRO; SINGH, N JOHNSON; SINGH, SUKHAM JOYBI (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during winter (rabi) season of 2021–22 and 2022–23 at Krishi Vigyan Kendra, Churachandpur, (ICAR-Research Complex for NEH Region, Manipur), Manipur, to assess the yield, soil fertility, and economics of ’Arka Samrat’ tomato (Solanum lycopersicum L.) variety compared to farmers’ practices at six locations. The implementation of SSNM significantly enhanced soil fertility parameters, with marked improvements in soil organic carbon, SOC stock, N, P and K levels, whereas soil bulk density and pH remained unaltered. Agronomic performance was satisfactory, with yields averaging 20 t/ha across demonstration sites. Economic analysis revealed financial viability, with a mean gross return of ₹303,000/ha against a production cost of ₹97,800/ha, yielding an average net return of ₹210,500/ha. The benefit-cost ratio of 3.09 and return on investment of 2.15 accentuate the economic efficacy of the intervention. Additional economic indicators productivity per unit area (1,330), break-even point (8,150), marketable surplus (3,261), and marginal rate of return (222) further validate the financial reliability of the approach. This investigation establishes that SSNM-based tomato cultivation represents an agronomically viable and economically profitable enterprise for the sub-tropical hills of Manipur, offering a sustainable pathway to enhanced soil fertility, optimized yields, and improved agricultural livelihoods in this distinctive agroecological zone.